Ecophysiological study on the Pacific oyster Crassostrea gigas naturally infected by a Chlamydia-like microorganism : effect of infection level and diet on oyster physiological responses - Soletchnik, Patrick; Goulletquer, Philippe; Cochennec, Nathalie; Renault, Tristan; Geairon, Philippe (Société Française de Malacololgie, 1998)
A population of Pacific ovsters, Crassostrea gigas, infected with a Chlamydia-like procaryote was reared to compare infection trends under three different feeding conditions: a starved condition, an intermediate condition with a diet of Skeletonema costatllm, and a mixed algal diet. Several physiological and pathological criteriJ: presence of gill abnormality; microscopic examination, basophilic intracytoplasmic inclusions, Feulgen reaction; condition index, filtration, food consumptiQn; fecal production and respiration were used to compare the various modalities one month after the initiation of the experiment. The Irodality of starved oysters showed reduce physiological performances in terms of scope for growth and condition index compared to oysters fed Skeletonema costatlltm, or a mixed diet of Isoclll:ysis galbana (Tahitien strain), TetraseJmis sllecica, Chaetoceros calcitrans and Pavlova llitherii. A condition index of 7.4 reflected a prespawning stage in the population fed with a diet of mixed algae. Although infected with a Chlamydia-like microorganism, impres6ive physiological responses (good condition index and positive scope for growths) were reported for both fed oyster populations. The scope for growth values compared to effective production were discussed with regard to the maturation process and the pre-spawning stage of the oysters. A positive linear relationship was, established between gill abnormalities and filtration rate for starved and Skeletonema fed oysters. In populations known to be infected with the Chlamydia – like organism examined in this study, clearance rate estimates represent a better bioindicator for high infection level than compared to either physiological measurements (e.g., respiration, feces production) or estimates (e.g., absorption rate, scope for growth). Thus, the relationship between pathological criteria and physiological measurements can be used to estimate pathogen diagnosis. However, specific pathogen identifications should be carried out as a further step to ...